Using In Silico Methods to Identify Protein Tyrosine Kinase A (PtkA) Homolog in Non-Tuberculous Mycobacteria (NTM) - Swati Jaiswal; Sanjay Kumar (Kinases and Phosphatases)
Non-tuberculous mycobacteria (NTM) represent a diverse group of mycobacterial species known for causing opportunistic infections, especially in individuals with underlying health conditions. Unlike Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis, NTM species exhibit different pathogenic characteristics and drug resistance mechanisms, making them increasingly relevant in clinical settings. PtkA is a crucial protein tyrosine kinase that regulates bacterial growth, stress response, and virulence by phosphorylating various substrates in Mtb. Understanding whether PtkA homologs exist in NTM could provide insights into their virulence and resistance mechanisms. In silico approaches, which utilize computational tools for sequence alignment, structure prediction, and functional annotation, offer a powerful means to identify homologous proteins across different species. In this article, we have employed tools like BLAST (Basic Local Alignment Search Tool), protein structure databases, and the NTM database to identify PtkA homologs in NTM genomes, providing a foundation for further studies.